Rút gọn biểu thức : P = $\frac{2\sqrt{x}}{x-1}$ – $\frac{1}{1-\sqrt{x} }$ + $\frac{\sqrt{x}}{\sqrt{x}+1}$ ( x ≥ 0 , x $\neq$ 1)

Question

Rút gọn biểu thức :
P = $\frac{2\sqrt{x}}{x-1}$ – $\frac{1}{1-\sqrt{x} }$ + $\frac{\sqrt{x}}{\sqrt{x}+1}$ ( x ≥ 0 , x $\neq$ 1)

in progress 0
Vivian 3 ngày 2021-12-07T18:11:43+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-12-07T18:13:15+00:00

    Đáp án:

    $P = \dfrac{\sqrt x +1}{\sqrt x – 1}$

    Giải thích các bước giải:

    $\begin{array}{l}P = \dfrac{2\sqrt x}{x – 1} -\dfrac{1}{1-\sqrt x} +\dfrac{\sqrt x}{\sqrt x + 1}\qquad (x \geq 0;\, x \ne 1)\\ \to P =\dfrac{2\sqrt x}{(\sqrt x -1)(\sqrt x+1)} + \dfrac{\sqrt x+1}{(\sqrt x -1)(\sqrt x+1)} + \dfrac{\sqrt x(\sqrt x -1)}{(\sqrt x -1)(\sqrt x+1)}\\ \to P = \dfrac{2\sqrt x + \sqrt x + 1 +x – \sqrt x}{(\sqrt x -1)(\sqrt x+1)}\\ \to P = \dfrac{ x + 2\sqrt x+1}{(\sqrt x -1)(\sqrt x+1)}\\ \to P = \dfrac{(\sqrt x + 1)^2}{(\sqrt x -1)(\sqrt x+1)}\\ \to P = \dfrac{\sqrt x+1}{\sqrt x – 1}\end{array}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )